How to manage global partner relationships to achieve sustainability goals: A decision support system using the Best-Worst Method and applied to cargo airlines - Verwer, Tim P; Kamp, Linda M (Journal of Supply Chain Management Science, 2024)
The urgency of sustainability in aviation has led to a focus on operational activities, especially in the global supply chain of cargo airlines. This study introduces a Decision Support System (DSS) to improve Partner Relationship Management. The DSS helps partners work toward sustainability goals. It uses the Best-Worst Method in a Multi-Criteria Decision-Making framework. The DSS segments partners based on their sustainability capabilities and willingness. It also proposes targeted strategies. The system was applied to a cargo airline aiming for zero emissions and zero waste, managing Ground Handling Agents across 168 outstations. The application showed the effectiveness of partner segmentation, with most partners demonstrating high capability and willingness. A step-by-step strategy was developed to implement sustainability practices, including a checklist for performance assessment. The study concludes that the DSS and strategy offer a structured and actionable approach that can be adapted for other cargo airlines. Future research is recommended to validate the DSS in other industries, explore alternative segmentation methods, and refine strategies considering partner size and impact.